Musical Composition “Segehan Wong” | Komposisi Karawitan “Segehan Wong” - I Gusti Ngurah Wisnu Dharma Gung Wisnu; I Nyoman Sudiana (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
Segehan Wong is an ceremony or offering where the offering is a symbol as a form of resistance for Hindus in Bali against the Covid-19 Virus, which is expressed in the form of innovative musical works presented with Balinese gamelan. Where has parts where in the first part it is the head of the segehan which is white which means that the negative thought can be overcome by holiness is continued to the second part which is in the segehan contained in the body colored brumbun has meaning so that all feelings are present and radiate from the deepest heart and also include the two hands where the left hand is yellow which means glory and the right hand is red which means courage and in the third part covers the feet of segehan which is black which means black. has the meaning of daring to step through the darkness of the present world.